High-Resolution 3D Shear-Wave velocity structure in xiong’an New Area, Beijing (China), revealed by short-period dense seismic array - Liu, Qiaoxia; Xu, Zhiping; Zhou, Ming; Duan, Yonghong; Qiu, Yong; Feng, Chengjun; Zhu, Shuaipeng; Wang, Chongpeng; Chen, Minjie (Journal of Asian earth sciences, 2025)
[Display omitted] •We obtain 3D Vs model with ∼ 1 km resolution of Xiong’an New Area based on short-period dense array.•Our model provides new evidence to solve some controversial issues on the pre-existing faults.•We propose a new technical idea for geothermal resources prospecting based on 3D Vs model. The 3D shear-wave velocity (Vs) structure in the shallow crustal of Xiong’an New Area can reveal the sediment characteristics and the tectonic features of the blind faults. They are essential for earthquake hazard reduction and geothermal resource exploration in urban areas. The dense array detection method has proved to be an effective technology tool for obtaining the 3D Vs model of the urban area. Using the seismic ambient noise recorded by Xiong’an dense array, we separately conducted the frequency-Bessel transform method and the fast marching technology to estimate short-period (0.4–2.4 s) and long-period (2.5–6 s) fundamental Rayleigh wave phase velocity dispersions. By jointly inverting these dispersions, we finally obtain a fine shallow-deep (0–5 km) 3D Vs model. Our Vs structure correlates well with the tectonic units and reveals the overall stability of the shallow crust structure of the Xiong’an New Area. We extract 3D depths distribution characteristics of the Quaternary and Neogene bottom boundaries from 3D Vs model, which respectively indicates that the Xiongan New Area has been in a relatively stable tectonic position since the Cenozoic. We also provide new evidence to further determine the buried depth and extension patterns of the pre-existing faults or unconformable contact interfaces. Lastly, we analyze and summarize the 3D characteristics of structural sedimentary and potential geothermal exploration areas through conducting comprehensive analysis and interpretation of the regional terrestrial heat flow and geological drilling, which propose a new technical idea for the prospecting and assessing of the geothermal resources based on 3D Vs model.